Actinic cheilitis: A review - Elangovan Somasundaram; Ruchi Gera; Harish Babu Peethambaran (Wolters Kluwer Medknow Publications, 2015)
Actinic cheilitis (AC) is a chronic inflammatory disorder of the lips that is caused by prolonged exposure to sunlight in susceptible individuals. It affects the vermilion region of the lower lip almost exclusively. UV-B rays with a wavelength of 290-320 nm are held responsible for the sunlight-induced damage. The exact mechanism of the development of AC is unclear. It is considered to be potentially malignant.